ANALYSIS OF PROFESSIONALISM, COMPETENCY AND INDEPENDENCE ON AUDIT QUALITY IN PUBLIC ACCOUNTING FIRM IN PALEMBANG CITY. - Adin, Adindia; Nurmala; Panca Satria Putra (Universitas Indo Global Mandiri Palembang, 2024)
Objective: This is to determine the effect of professionalism, competency and independence analysis on audit quality at Public Accounting Firms in Palembang. ” Design/method/approach: